Double Bolus Alteplase Therapy during Cardiopulmonary Resuscitation for Cardiac Arrest due to Massive Pulmonary Embolism Guided by Focused Bedside Echocardiography - Hafiz B. Mahboob; Bruce W. Denney (Case Reports in Critical Care)
Massive pulmonary embolism (PE) frequently leads to cardiac arrest (CA) which carries an extremely high mortality rate. Although available, randomized trials have not shown survival benefits from thrombolytic use. Thrombolytics however have been used successfully during resuscitation in clinical practice in multiple case reports and in retrospective studies. Recent resuscitation guidelines recommend using alteplase for PE related CA; however they do not offer a standardized treatment regimen. The most consistently applied approach is an intravenous bolus of 50 mg tissue plasminogen activator (t-PA) early during cardiopulmonary resuscitation (CPR). There is no consensus on the subsequent dosing. We present a case in which two 50 mg boluses of t-PA were administered 20 minutes apart during CPR due to persistent hemodynamic compromise guided by bedside echocardiogram. The patient had an excellent outcome with normalization of cardiac function and no neurologic sequela. This case demonstrates the benefit of utilizing bedside echocardiography to guide administration of a second bolus of alteplase when there is persistent hemodynamic compromise despite achieving return of spontaneous circulation after the initial bolus, and there is evidence of persistent right ventricle dysfunction. Future trials are warranted to help establish guidelines for thrombolytic use in cardiac arrest to maximize safety and efficacy.